Optimisation of manufacturing processes a response surface approach - Evans, Mark (Maney for the Institute of Materials, Minerals and Mining, 2003)
Many engineering companies around the world are currently undergoing a quality control and improvement revolution that originally started in Japan many decades ago and this book provides a brief overview of this revolution. Robust design is a central component of the modern approach to quality improvement and is a phrase used to describe any engineering activity whose Robust design is a central component of the modern approach to quality improvement and is a phrase used to describe any engineering activity whose objective is to develop high quality products (and processes) at low cost. A key c.
Keywords: Production planning.; Experimental design.; Quality control.; elektronické knihy; electronic books